IDENTIFIKASI KESULITAN SISWA DALAM MEMAHAMI MATA PELAJARAN EKONOMI PADA SISWA KELAS X IIS 1 DI SMA ISLAM KEPANJEN SEMESTER GENAP TAHUN AJARAN 2013/2014 - Aulia Nur Rosyidah; Mit Witjaksono; Ro'ufah Inayati (Universitas Negeri Malang, 2015)
This research was conducted with the aim to describe some of the things that include student difficulties in understanding the Economics subject and efforts to overcome the problems for the tenth grade students of Social Studies 1 at SMA Islam Kepanjen. This research is a qualitative descriptive study. Checking the validity of data use a tringulation. Based on the analysis of data obtained in the study area, it obtained 4 following conclusions: (1) students’ difficulty in understanding the Economics material is only on the material of SHU (Business Profits) calculation. (2) the cause of the students’ difficulties in understanding the economy material is influenced by several reasons such as: first, the lack of interest of students to study Economics. Second, students do not have books or text books to support economic study, which owned only the record books. Third, students are burdened with too much school work, so that students find it hard to learn and eventually lazy to learn Economic. Fourth, students are less able to understand the material surrounding Economic existing calculation formula, such as the material count of Business (SHU). Fifth, the potential intelligence of students who have difficulty in understanding the material is included in the category Economy average down. Students who are potential intelligence belonging to the low could be difficulty in learning the material calculating, especially if the count was a lot.; (3) the efforts of students in overcoming the difficulty in understanding the Economic subject to study in groups with class mates who are more familiar and ask for help or ask the teacher a field of study that described the material back and taught the ways of solving problems calculating the SHU; (4) the efforts of teachers in overcoming the students’ difficulties in understanding the Economics subject is first, by giving assistance during the process of learning in the classroom is the teacher explains the return of material that has not been understood by the students because it can help students to learn the material, and so students can finish practice questions that had been given. Second, teachers also provide motivation during the learning process in the classroom by way of gift giving. Giving gifts is done so that students are more eager to learn Economics, so that students can take pleasure in learning in the classroom.